Probing Coupled Rotational and Electronic Dynamics during Laser-Induced Molecular Fragmentation - Guo, Keyu; Hu, Xiaoqing; Li, Min; Jia, Cong-Cong; Zhang, Songbin; Cao, Chuanpeng; Xie, Wenhai; Cao, Wei; Liu, Kunlong; Zhou, Yueming; Wu, Yong; Wang, Jianguo; et al. (Ultrafast science, 2024)
Coupled nuclear and electronic dynamics within a molecule are key to understanding a broad range of fundamental physical and chemical processes. Although probing the coupled vibrational and electronic dynamics was demonstrated, it has so far been challenging to observe the coupling interactions between the rotational and electronic degrees of freedom. Here, we report the first observation of Coriolis coupling, a coupling interaction between nuclear rotational angular momentum and electronic axial angular momentum, during laser-induced molecular fragmentation by tracing the electronic structure of a dissociating O 2 + molecule. We observe that the electron density changes its shape from that of a molecular σ orbital to a nearly isotropic shape as the internuclear distance goes up to ∼20 Å, which results from the transition between nearly degenerate electronic states associated with different rotational angular momenta. Our experiment demonstrates that the breaking of a chemical bond does not occur suddenly during molecular dissociation. Instead, it lasts for a long time of several hundred femtoseconds due to the Coriolis coupling interaction. Our experiment can be extended to complicated molecules, holding the potential of revealing yet unobserved electron–nuclear coupling interactions during ultrafast processes.